EFISIENSI TEKNIS PRODUKSI KEDELAI BERDASARKAN VARIETAS DAN WILAYAH PRODUKSI DI INDONESIA - Medita Ivanni; Nunung Kusnadi; Suprehatin Suprehatin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2019)
The improvement of production efficiency to increase the soybean production is necessary in this recent time. Increasing the soybean production can be done with the intensification and extensification program. This purpose of study is to analyze the technical level of soybean’s efficiency based on variety and production area in Indonesia and the factors that determinated it. This study used BPS data in five main soybean production area with 3 038 farmer observation. This research used Cobb Douglass stochastic frontier to analyze the production function. The result showed that soybean production based on variety and production area were efficien except outside Java. The production efficiency determined by type of land and farmer groups.